The Mystical World of the Body in the Bengali Tantric Work Nigūḍhārthaprakāśāvali - Czyżykowski, Robert (Religions, 2020)
Amongst the wide collection of literature on the Bengali Tantric Vaiṣṇava Sahajiyās, the works of Mukundadāsa (or Mukundadeva) and his disciples are counted among the most influential. Those Middle Bengali texts that are usually recognized as a group of the four main texts of Mukunda and his circle or followers are commented in the work Nigūḍhārthaprakāśāvali (NPV, ‘The Array of lights on the hidden meanings’) by various disciples of this line. The main goal of this paper is to shed light on some aspects of the religious experience in the regional Tantric tradition. As we may suppose, the descriptions included in NPV refer to some previous experiences of the authors (gurus) of the tradition and describe imaginary internal worlds of the body in the manner specific to that tradition, using various esoteric terms and describing also various kinds of religious discipline (sādhana). This means the presentation of the relatively poorly known and still not well-studied Bengali Tantra is expressed in the vernacular Bengali language (Middle Bengali, madhyajuger Bānglā). I will try to demonstrate how the image of the human body (and its imagination in this particular tradition) serves as the basis for the religious experience.